1974
DOI: 10.1111/j.1365-2621.1974.tb02896.x
|View full text |Cite
|
Sign up to set email alerts
|

Certain Functional Properties of Sunflower Meal Products

Abstract: Certain functional properties including water absorption, fat absorption, emulsification, whippability and foam stability were determined on the sunflower flour, protein concentrates and isolate. The results were also compared to those obtained on soy products. Data on water and fat absorption studies suggest that soy products are more hydrophilic in nature while sunflower material exhibited greater lipophilic properties than the soy products. Emulsification tests showed that sunflower flour was superior to al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

47
454
9
21

Year Published

1997
1997
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 811 publications
(531 citation statements)
references
References 8 publications
47
454
9
21
Order By: Relevance
“…With 0 M sodium chloride, EA values of walnut protein isolates, concentrates and DWF was 50.9%, 52.3% and 52.7%, respectively, which were comparable to cowpea protein isolate (Ragab et al 2004), sesame protein isolate (Khalid et al 2003). This is in agreement with Kinsella et al (1985), who stated that the emulsifying capacity of proteins tends to decrease as protein concentration is increased, and this is also consistent with the similar reported observations on winged bean protein concentrate (Sathe et al 1982), and sunflower protein isolate (Lin et al 1974). The change in ES was similar to that of EA, except that ES value of walnut protein isolates was higher than that of walnut protein concentrates, which was higher than that of DWF at different sodium chloride concentrations (0-1.0 M).…”
Section: Resultssupporting
confidence: 90%
“…With 0 M sodium chloride, EA values of walnut protein isolates, concentrates and DWF was 50.9%, 52.3% and 52.7%, respectively, which were comparable to cowpea protein isolate (Ragab et al 2004), sesame protein isolate (Khalid et al 2003). This is in agreement with Kinsella et al (1985), who stated that the emulsifying capacity of proteins tends to decrease as protein concentration is increased, and this is also consistent with the similar reported observations on winged bean protein concentrate (Sathe et al 1982), and sunflower protein isolate (Lin et al 1974). The change in ES was similar to that of EA, except that ES value of walnut protein isolates was higher than that of walnut protein concentrates, which was higher than that of DWF at different sodium chloride concentrations (0-1.0 M).…”
Section: Resultssupporting
confidence: 90%
“…Soybean (Glicina max (L.) Merril) flour and protein concentrate had an increase of 70 and 170%, respectively, in the volume of foam (LIN et al, 1974).…”
Section: Discussionmentioning
confidence: 99%
“…Water (WAC) and oil (OAC) absorption capacities were determined according to the method of LIN et al (1974) and calculated by the difference between the total volume and the free volume.…”
Section: Water and Oil Absorption Capacitiesmentioning
confidence: 99%
“…Besides, it might be due to the higher protein solubility of soy flour protein as reported [47] who found that the protein solubility of co mmercial soy flour was 21.4%. Meanwh ile, there was a significant difference in co mparison within each treatment in most of cases except t reat ments which had carrageenan and carboxy methyl cellulose.…”
Section: Total Volatile Basic Nitrogen (Tvbn)mentioning
confidence: 94%